Manuel Castells the theory of the network society - Stalder, Felix 1968- (Polity, 2006)
For the past three decades, Manuel Castells has been at the forefront of debates about contemporary social transformations. This book provides the first in-depth study of Castells' entire body of work.
Includes bibliographical references (p. [241]-251) and index
Keywords: Castells, Manuel; Castells, Manuel -- 1942-; Sociologie; Soziologie; Information society; Social movements; Globalisierung; Kapitalismus; Soziale Bewegung; Informationsgesellschaft